PEMBINAAN PENGELOLAAN MANAJEMEN KEUANGAN DAN DIGITAL MARKETING DALAM MENINGKATKAN PENDAPATAN USAHA PADA IKM PAPUA MUDA KREATIF KELURAHAN AWIYO DISTRIK ABEPURA - Endah Dwi Lestari; Yoseb Boari; Diana Yulia Paula; Maria Apriyane Patty (Jurnal Pengabdian Masyarakat Nusantara, 2022)
Red Ginger is used by the community as an herbal medicine that serves to increase endurance and is able to overcome sore throat, flu and fever as well as stomach disorders. The increasing public interest in consuming red ginger, especially during the Covid-19 pandemic was be an opportunity for small business owner to make processed products made from ginger with economic value, namely herbal drinks in the form of instant powder. The purpose of this Community Service activity was to provide training on Financial Management and Digital Marketing as an effort to increase business income for instant ginger powder drinks at IKM Papua Muda Kreatif. The methods used in this community service activity were the speech, discussions and training on financial management, making simple financial reports, digitalization marketing strategies and the use of social media to support promotional and marketing activities. The result of this community service activity that IKM Papua Muda Kreatif was able to make simple financial reports and utilize digital marketing as a marketing strategy to increase business income.